1997
DOI: 10.1007/s004600050140
|View full text |Cite
|
Sign up to set email alerts
|

Pump/probe direct photoionization from thermally hot samples: the Cs2 molecule

Abstract: We investigate the femtosecond photoionization of Cs 2 within a model including four electronic states. A thermally broad initial state distribution influences the timedependence of the transient ion signals crucially. We show that even for the present case of simple one-dimensional motion the interpretation of ionization signals requires special care under certain experimental conditions. The results are compared to recent experimental data and a modified ionic state potential is constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…88 In 1997, Braun and Engel considered the role of initial temperature of the ground state in TRPES, using the hot cesium dimer as an example. 89 In 1998, Meier and Engel explicitly considered the important role of frequency chirp (i.e., the time ordering of frequencies in a broad bandwidth pulse) in fs TRPES experiments, relevant to the discussion of quantum coherent control in this area. 90 In 1997, T. Seideman developed a formal nonperturbative theory of time-resolved PADs.…”
Section: Theoretical Developmentsmentioning
confidence: 99%
“…88 In 1997, Braun and Engel considered the role of initial temperature of the ground state in TRPES, using the hot cesium dimer as an example. 89 In 1998, Meier and Engel explicitly considered the important role of frequency chirp (i.e., the time ordering of frequencies in a broad bandwidth pulse) in fs TRPES experiments, relevant to the discussion of quantum coherent control in this area. 90 In 1997, T. Seideman developed a formal nonperturbative theory of time-resolved PADs.…”
Section: Theoretical Developmentsmentioning
confidence: 99%
“…Joint experimental and theoretical studies of multiphoton ionization processes on K 2 , Cs 2 , , and Li 2 138 revealed similarities and differences with processes found in Na 2 , which stem from different characteristic features of the PES for excited states of neutral and cationic species of these systems as well as from experimental conditions. Furthermore, the fs-dynamics of mixed dimers, such as the vibrational wave packet dynamics of the A 1 Σ + state of NaK 188 and its fractional revivals, has been investigated experimentally.…”
Section: 4 Full Quantum Mechanical Multistate Dynamics Of Small Syste...mentioning
confidence: 93%
“…For this purpose, eq 52 has to be used, in which the last term on the right-hand side can be modified by introducing the penalty factors which allow one to respect appropriate experimental conditions . For the transition dipole moments between the excited electronic states of the neutral species and the ground state of the cation, different approximations can be introduced. ,,, For example, the constant value of 5 D is in the range of transition dipole moments between electronic states of the neutral NaK and is sufficiently large to provide the robustness of the optimized pulses according to ref . The influence of the nuclear distance-dependent transition dipole moments should be tested.…”
Section: 2 Single-parameter and Multiparameter Control In Small Syste...mentioning
confidence: 99%
“…(iii) The objective of the optimal control is the maximization of the photoionization yield, and the target operator corresponds to the total occupation of the cationic states. For the transition dipole moments between the excited electronic states of the neutral species and the ground-state cation, different approximations have been performed. ,, , We used the constant value of 5 D since it is in the range of transition dipole moments between electronic states of the neutral NaK and is sufficiently large to provide the robustness of the optimized pulses according to ref and our experience. The influence of the nuclear distance-dependent transition dipole moments which are available for NaI in the literature 19 has been tested and found to be negligible.…”
Section: Theoretical Methods and Experimental Conditionsmentioning
confidence: 99%
“…Advances achieved in pulse-shaping techniques opened new roads in the field, in particular concerning the control of chemical reactivity in complex systems. However, the investigation of simple systems offers a possibility to learn how to use the control as a tool for analyzing the underlying processes. Therefore, metallic dimers and diatomic molecules , have been studied in numerous contributions, since they are suitable model systems for verifying the scopes of different control schemes and they are accessible to experimental pulse shaping techniques. Theoretical and experimental work using two-parameter control has been performed: In addition to the pump−probe time delay, the second control parameter involved the pump 10,21-22 and/or probe 11,14 wavelength, the pump−dump delay, , the laser power, the chirp, , or temporal width 19 of the laser pulse. Optimal pump−dump control of K 2 has been carried out theoretically in order to maximize the population of certain vibrational levels of the ground electronic state using one electronic excited state as an intermediate pathway. Concerning optimal control for the maximization of the ionization yield in alkali dimers, the experimental work using evolutionary algorithms 26-32 has prompted the theoretical investigations presented here.…”
Section: Introductionmentioning
confidence: 99%